Integrating multimedia learning theory in assistive courseware for low vision learners - Aziz, Nurulnadwan; A. M., Ariffin; Sarif, Siti Mahfuzah (Penerbit UTM Press, 2015)
This paper reports an ongoing study regarding the development of Assistive Courseware (AC) that is specifically designed to cater the needs of low vision learners in learning activities.Currently, as reported in the previous studies, low vision learners are facing various difficulties in their learning activities particularly in terms of information accessibility, navigationability, and pleasure. Previous literatures also state that, most of the available courseware means too little to them especially in terms of content presentation.Therefore, this study attempts to solve the problem by developing an AC which is named as AC for Low Vision Learners (AC4LV). The AC was developed by utilizing Multimedia Learning Theory as guidance. In addition, three basic steps, which are pre-production, production, and post-production have been utilized in developing the AC.As a result, an AC4LV based on Multimedia Learning Theory was successfully produced. Future works of this study is to test the experience of using AC4LV among the low vision learners particularly on primary school children from age nine to twelve.